2022
DOI: 10.1021/acs.jpca.2c01774
|View full text |Cite
|
Sign up to set email alerts
|

The Radiation Chemistry of NH3···CO Complex in Cryogenic Media as Studied by Matrix Isolation

Abstract: The NH3···CO complex can be considered an important building block for cold synthetic astrochemistry leading to the formation of complex organic molecules, including key prebiotic species. In this work, we have studied the radiation-induced transformations of this complex in Ar, Kr, and Xe matrices using FTIR spectroscopy. On the basis of comparison with the quantum chemical calculations at the CCSD­(T)/L2a_3 level of theory, it was found that the initial complex had the configuration with hydrogen bonding thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…[124] reporting the formation of H 2 NCO • and NCO • radicals under UV-photolysis of HNCO in a solid Xe matrix. In our recent FTIR spectroscopic study [125], it was shown that both these radicals were produced after X-ray irradiation of the NH 3 /CO/Ng (Ng = Ar, or Kr) deposited mixture at 5 K. It was concluded that the H 2 NCO • radical resulted from the NH 3 • • • CO intermolecular complex (the detailed mechanism is unclear), while the NCO • radical was formed though subsequent dehydrogenation of H 2 NCO • [125]. Synthetic processes of such kind may be generally important for understanding the mechanisms of the formation of COMs with amide moiety in mixed astrochemical ices subjected to ionizing radiation.…”
Section: Cno-containing Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[124] reporting the formation of H 2 NCO • and NCO • radicals under UV-photolysis of HNCO in a solid Xe matrix. In our recent FTIR spectroscopic study [125], it was shown that both these radicals were produced after X-ray irradiation of the NH 3 /CO/Ng (Ng = Ar, or Kr) deposited mixture at 5 K. It was concluded that the H 2 NCO • radical resulted from the NH 3 • • • CO intermolecular complex (the detailed mechanism is unclear), while the NCO • radical was formed though subsequent dehydrogenation of H 2 NCO • [125]. Synthetic processes of such kind may be generally important for understanding the mechanisms of the formation of COMs with amide moiety in mixed astrochemical ices subjected to ionizing radiation.…”
Section: Cno-containing Radicalsmentioning
confidence: 99%
“…In this situation, the pre-existing building blocks consisting of two or more molecules should play a crucial role. In order to understand the basic mechanisms involved in the processes of cold synthetic transformations, we have introduced a general concept based on model studies of the radiation chemistry of 1:1 intermolecular complexes isolated in rigid inert media [94,95,112,117,125,134,[136][137][138][139][140][141]. It should be emphasized that the interaction in such complexes is typically rather weak (the computed interaction energy usually does not exceed 2-4 kcal/mol); however, it is more than sufficient to fix the pre-determined geometry in solid cryogenic matrices, and thus, to control further radiation-induced transformations.…”
Section: Identification Of Radical-molecule Complexes and Their Possi...mentioning
confidence: 99%
“…Purely theoretical studies are providing characterization for other unique molecules including glycolic acid, pyridyl radicals, and diazirine along with its cyclic isomers . Additionally, the molecular structure and spectra of noncovalent interactions are also characterized through a mixture of theory and experiment for glycerol–water clusters, HCN and CH 3 Cl clusters, and complexes of NH 3 ···CO …”
mentioning
confidence: 99%
“…16 Additionally, the molecular structure and spectra of noncovalent interactions are also characterized through a mixture of theory and experiment for glycerol−water clusters, 17 HCN and CH 3 Cl clusters, 18 and complexes of NH 3 •••CO. 19 The extreme conditions of various astrophysical environments also open novel chemistry. However, such reactions can only be interrogated through the use of emerging and cuttingedge experimental and theoretical techniques.…”
mentioning
confidence: 99%